From Advice to “Secret Mandates”: The Evolution of Government Intervention in Public-Sector Bargaining in Alberta, Canada - Foster, Jason; Barnetson, Bob; Cake, Susan (Relations industrielles / Industrial Relations, 2024)
SummaryGovernments in Canada are increasingly using multiple tools to advance their political agenda at the expense of free collective bargaining in the public sector. Legislative intervention has long been a strategy to curtail bargaining rights (Evans et al., 2023). Recently, governments have turned to non-legislative means to influence bargaining outcomes. This article is about the use of a coordination office, a decidedly non-legislative tactic, and how, over two rounds of negotiations, it transformed public-sector bargaining in Alberta. Bargaining has been further transformed by enactment of a legal requirement to keep the government’s mandates secret, the outcome being increased frustration among union representatives and potential damage to long-term relationships. Together, these measures have provided the government with a powerful means of influence, which, if successful, could spread to other jurisdictions.